The Malay version of the Michigan hand outcomes questionnaire: cross-cultural adaptation, validation and reliability testing - Lye, Jun Xiong; Kow, Ren Yi; Ismail, Raffael; Khalid, Kamarul Ariffin (World Scientific, 2021)
Background: The Michigan Hand Outcomes Questionnaire (MHQ), a self-reported questionnaire for patients with hand disorders, has been widely used globally. It has been cross-culturally adapted into different languages across all continents. Aims of this study were to translate the MHQ into Malay language and to evaluate its reliability and validity compared with Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire in a Malay-speaking population. Methods: The MHQ was cross-culturally adapted into a Malay version based on the guidelines. A pre-testing involving thirty pa tients with hand disorders was performed to assess whether it was comprehensible to the target population. One hundred patients with hand disorders were recruited in this study to answer the MHQ and DASH questionnaires. The MHQ was tested twice with an interval of two weeks in between. Statistical analysis was performed to assess the reproducibility and internal consistency via the test-retest method and Cronbach’s alpha calculation, respectively. The association between MHQ and DASH questionnaire was assessed with Spearman’s correlation calculation. Results: In the pre-testing, twenty-six patients (86.7%) understood all the questions in the Malay version of MHQ. The test-retest analysis showed a good reliability across the duration of two weeks with the intraclass correlation coefficient of all subscales ranging from 0.925 to 0.984. Cronbach’s alpha values of the Malay version MHQ ranged from 0.82 to 0.97, indicating a good inter nal consistency. Spearman’s correlation factor of the MHQ in comparison with DASH showed a fair to moderately strong correla tion with the values ranging from 0.513 to 0.757. Conclusions: The Malay version of MHQ was successfully translated and culturally-adapted with excellent reliability (reproduc ibility and internal consistency) and good construct validity.